Implementasi Pembelajaran Akidah Akhlak dalam Pembentukan Karakter Disiplin Siswa Madrasah Ibtidaiyah - Siti Halimatus Sa’diyah; Aulia Ainindia Wanti; Asnal Mala (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
The purpose of a disciplined attitude is to enhance the quality of ethics, mental strength, responsibility, self-control, good personal habits, assertiveness, and obedience to rules. The aim of this study is to examine the implementation of Aqidah Akhlak learning in the formation of disciplined character among Madrasah Ibtidaiyah students. This research uses a qualitative research method. Data collection techniques utilize literature study techniques. Data analysis techniques are presented using content analysis techniques. The research results prove that Aqidah Akhlak learning is aimed at shaping the disciplined attitude of students in Madrasah Ibtidaiyah, starting with teachers preparing teaching modules to make learning more directed and organized. Teachers also create motivation, provide constructive guidance, assertiveness, and serve as role models for students to emulate. The situation and condition of the classroom will make students comfortable to learn when they have a disciplined character. Creating a conducive environment in the classroom can help teachers explain the learning material effectively without difficulties, and assist students in understanding it easily.